Novel industrial ecosystems and value chains to utilize side-streams of wood products industries – Finnish approach - Verkasalo, Erkki; Leppälä, Jarkko; Muhonen, Timo; Korpinen, Risto; Möttönen, Veikko; Kurppa, Sirpa (Editura Universitatii Transilvania din Brasov, 2019)
Side-streams of wood product industries such as wood chips, planer shavings, saw dust, sanding dust, off-cut pieces, bark and liquid and gaseous wastes considerably contribute to cascading, sustainability and carbon balance as well as profitability of saw mill, plywood and further processing industries in northern Europe. They are important raw materials for pulp and paper, wood panel and bioenergy industries, and provide much basis for novel value-added products. Industrial ecosystems based on side-streams may be integrated with pulp and paper mills, chipboard or fibreboard mills or heating and power plants, concentrated to SME industry parks or decentralized between feedstock terminals, wood processing mills and biorefinery plants of different size. Availability and flows of raw materials and semi-finished products, enterprise network and collaboration, storage and transportation logistics and scaling of production essentially affect the optimal build-up of industrial ecosystems and value-add. The objective of this paper is to summarize results from our recent state-of-art and future perspective studies in Finland regarding industrial ecosystems based on side-streams of wood product industries. We stress here value and supply chains, scaling production, business and ownership, and present examples on well-functioning industrial ecosystems and enterprise networks in Finland.
Keywords: wood product industries; side streams; added value; industrial ecosystem; value chains